Use of mixed wastewaters from piggery and winery for nutrient removal and lipid production by Chlorella sp. MM3. (May 2018) - Ganeshkumar, Vimalkumar; Subashchandrabose, Suresh R.; Dharmarajan, Rajarathnam; Venkateswarlu, Kadiyala; Naidu, Ravi; Megharaj, Mallavarapu
Highlights: Mixed wastewaters of piggery and winery were treated by Chlorella sp. MM3. Strain MM3 grew well in 20:80 ratios of piggery and winery wastewaters. Microalga removed 89% of total nitrogen and 49% of phosphates from 20:80 mixtures. Algal growth in 20:80 of piggery and winery wastewaters yielded 51% lipid. First report on bioremediation of both the wastewaters in a mixture by a microalga. Abstract: The larger-scale generation of piggery and winery wastewaters and consequent eutrophication are quite alarming, necessitating the use of a cost-effective treatment. This study attempted to remediate wastewaters from piggery and winery mixed in the ratios of 20:80, 50:50, 80:20, 100:0 and 0:100, in terms of nutrient removal and subsequent lipid accumulation by soil microalga, Chlorella sp. MM3. The per cent removal of total nitrogen and phosphates by the alga from mixed wastewaters within 10-days ranged between 51 and 89 and 26–49, respectively. As determined by FTIR spectroscopy, the lipid accumulation in the microalgal cells grown in wastewater mixtures ranged between 29 and 51%. Our results suggest that Chlorella sp. MM3 could be a potential candidate for bioremediation of wastewaters derived from piggery farm and winery industry, and that mixing of these wastewaters in 20:80 ratio would be an efficient approach for phycoremediation of mineral-rich effluents and subsequent yield of fairly good amounts of biofuel.